Analgesic efficacy of an opioid-free postoperative pain management strategy versus a conventional opioid-based strategy following laparoscopic radical gastrectomy: an open-label, randomized, controlled, non-inferiority trial - Zhimin Lin; Zhongbiao Chen; Yongliang Li (World Journal of Surgical Oncology, 2024)
Abstract Objective In patients undergoing laparoscopic radical gastrectomy, the use of subcostal transversus abdominis plane block (STAPB) for completely opioid-free postoperative pain management lacks convincing clinical evidence. Methods This study included 112 patients who underwent laparoscopic radical gastrectomy at the 900TH Hospital of the Joint Logistics Support Force from October 2020 to March 2022. Patients were randomly divided into (1:1) continuous opioid-free STAPB (C-STAPB) group and conventional group. In the C-STAPB group, 0.2% ropivacaine (bilateral, 20 ml per side) was injected intermittently every 12 h through a catheter placed on the transverse abdominis plane for postoperative pain management. The conventional group was treated with a conventional intravenous opioid pump (2.5 μg/kg sufentanil and 10 mg tropisetron, diluted to 100 ml with 0.9% NS). The primary outcomes were the accumulative area under the curve of the numeric rating scale (NRS) score at 24 and 48 h postoperatively at rest and during movement. The secondary outcomes were postoperative recovery outcomes, postoperative daily food intake, and postoperative complications. Results After exclusion (n = 16), a total of 96 patients (C-STAPB group, n = 46; conventional group, n = 49) were included. We found there were no significant differences in the cumulative AUC of NRS score PACU-24 h and PACU-48 h between the C-STAPB group and conventional group at rest [(mean difference, 1.38; 95% CI, − 2.21 to 4.98, P = 0.447), (mean difference, 1.22; 95% CI, − 6.20 to 8.65, P = 0.744)] and at movement [(mean difference, 2.90; 95% CI, − 3.65 to 9.46; P = 0.382), (mean difference, 4.32; 95% CI, − 4.46 to 13.1; P = 0.331)]. The 95% CI upper bound of the difference between rest and movement in the C-STAPB group was less than the inferior margin value (9.5 and 14 points), indicating the non-inferiority of the analgesic effect of C-STPAB. The C-STAPB group had faster postoperative recovery profiles including earlier bowel movement, defecation, more volume of food intake postoperative, and lower postoperative nausea and vomiting compared to conventional groups (P < 0.001). Conclusions After laparoscopic radical gastrectomy, the analgesic effect of C-STAPBP is not inferior to the traditional opioid-based pain management model. Trial registration ChiCTR2100051784.